1959
DOI: 10.1021/ac50164a010
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Controlled-Potential Coulometric Titrator

Abstract: Oak Ridge National laboratory, Oak Ridge, Tenn. b A simple electronic instrument for coulometric redox titrations a t controlled potential is described. The potential of only the electrode a t which the desired reaction occurs is controlled by a stabilized difference amplifier combined with a transistor current amplifier. The electrolysis current is integrated by a stabilized amplifier. The integral is read out a s a voltage. Either manual or automatic titrations may b e made. The instrument is alternating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

1964
1964
1984
1984

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Large-scale controlled potential electrolyses for spectrophotometry were carried out with a controlled-potential coulometer. 10 In this case the cell contents, after electrolysis, were transferred by gravity flow to the optical cell of a Cary Model 14 spectrophotometer. For transient optical spectra, a platinum gauze was placed directly in the optical path, and the controlled potential electrolysis was carried out in situ.…”
Section: Methodsmentioning
confidence: 99%
“…Large-scale controlled potential electrolyses for spectrophotometry were carried out with a controlled-potential coulometer. 10 In this case the cell contents, after electrolysis, were transferred by gravity flow to the optical cell of a Cary Model 14 spectrophotometer. For transient optical spectra, a platinum gauze was placed directly in the optical path, and the controlled potential electrolysis was carried out in situ.…”
Section: Methodsmentioning
confidence: 99%
“…Stop the titration and record the read-out voltage. The weight of europium (total) titrated is equal to the product of the read-out voltage and the europium coulometric factor, 6.315 mg. of Eu per volt (4,11).…”
mentioning
confidence: 99%
“…Although these polarographic studies indicate the feasibility of controlled potential reduction of N-oxides, quantitative studies have not been reported. EXPERIMENTAL Equipment-Controlled potential electrolyses were performed using an electronic controlled potential coulometric titrator, model Q-2005, ORNL (12). A Non-Linear Systems digital voltmeter, model 484 A, displayed the readout voltages.…”
mentioning
confidence: 99%